My quizzer in criminology : A reviewer - Manwong, Rommel K. (Quezon City : Wiseman's Books Trading Inc., 2011)
--Review questionnaires in criminal jurisprudence --Review questionnaires in law enforcement administration --Review questionnaires in criminalistics --Review questionnaires in criminal investigation and detection --Review questionnaires in criminal sociology, ethics & human relations --Review questionnaires in correction administration
Contents --Criminal jurisprudence --Law enforcement Administration --Criminalistics --Criminal investigation and detection --Criminal sociology, ethics & human relations --Correction Administration.
Inlcudes appendix.
Keywords: Crime -- Examinations